Lattice Design of a Compact Hadron Driver for Cancer Therapy. Issue 1 (1st February 2022) - Kwee Wah, Leo; Takayama, Ken; Adachi, Toshikazu; Kawakubo, Tadamichi; Dixit, Tanuja
Abstract: A next generation cancer therapy driver by using a fast-cycling induction synchrotron is given. The design of the lattice parameters with zero momentum-dispersion and high-flat momentum-dispersion region as essential parameters must be fulfilled and the optimization process with results are discussed here. Finally, the optimization process and method are developed and the lattice parameters are well defined.